2012
DOI: 10.1016/j.brs.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific facilitation of cognition by cathodal transcranial direct current stimulation of the cerebellum

Abstract: A role for the cerebellum in cognition is controversial, but it is a view that is becoming increasingly popular. The aim of the current study was to investigate this issue using transcranial Direct Current Stimulation (tDCS) during two cognitive tasks that require comparable motor skills, but different levels of working memory and attention. Three groups of twenty-two participants each performed the Paced Auditory Serial Addition Task (PASAT) and a novel variant of this task called the Paced Auditory Serial Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(201 citation statements)
references
References 53 publications
10
185
4
2
Order By: Relevance
“…Additionally, cortical folding produces polarity inversions of current flow and gyri and sulci produce the potential for current clustering (Datta et al 2009;Sadleir et al 2010). The cerebellum possesses both a disproportionally high density of neurons (Herculano-Houzel 2009), many of which are GABAergic (Galea et al 2009;Pope and Miall 2012), and a large degree of cortical folding (Herculano-Houzel 2009). Therefore, whilst certain limitations of the study prevent us from drawing definitive conclusions, it is perhaps not surprising that at 2 mA polarity appears to have little, if any, influence over the degree to which mood was modulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cortical folding produces polarity inversions of current flow and gyri and sulci produce the potential for current clustering (Datta et al 2009;Sadleir et al 2010). The cerebellum possesses both a disproportionally high density of neurons (Herculano-Houzel 2009), many of which are GABAergic (Galea et al 2009;Pope and Miall 2012), and a large degree of cortical folding (Herculano-Houzel 2009). Therefore, whilst certain limitations of the study prevent us from drawing definitive conclusions, it is perhaps not surprising that at 2 mA polarity appears to have little, if any, influence over the degree to which mood was modulated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that cerebellar tDCS produces behavioural and neurophysiological changes via excitation or suppression of its GABAergic Purkinje cell activity (Galea et al 2009). A reduction of CBI, with subsequent potentiated disinhibition of the cerebral cortex, has already been reported in response to cathodal stimulation of the right cerebellum (Block and Celnik 2013;Pope and Miall 2012;Galea et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found the cathodal TDCS to the cerebellum affected the performance of working memory tasks [84][85][86]. Finally, performance on a visuomotor adaptation task in healthy adults was improved by anodal TDCS [76].…”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%
“…The left cerebellum has a greater role in visuospatial processing and in spatial working memory [78]. The right cerebellum is more associated with verbal working memory particularly when tested using a digit span working memory task [85] or the Paced Auditory Serial Subtraction Task (PASST) evaluating working memory and attention [86]. …”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%
“…With regards to the cerebellum, this is partly because the lateral cerebellar hemispheres, which are thought to be involved in cognition (see below), are accessible to transcranial electrical stimulation, are sensitive to the effects of polarizing currents, and because the procedure is relatively inexpensive and easy to perform in human participants. The brain stimulation procedure described in the present article demonstrates how cognitive processes such as working memory and attention can be facilitated during tasks that are 'more' rather than 'less' cognitively demanding 1 . The interpretation of these task-specific results, are firmly constrained by an understanding of the physiology of the cerebro-cerebellar pathway.…”
Section: Introductionmentioning
confidence: 97%